Analysis of the English language as a universal medium of literal and professional communication worldwide (International Journal of Food and Nutritional Sciences, 2022)
English is a language of Europe with deep roots that continue to grow and blossom as communicative fruits. Since English is auniversaldialectal that is used and transcribed in the majority of nations both as a native language and as a secondary dilect, it is generally hard to thrive in the modernistic system of our planet without studying it. Additionally, it suggests exchanging a wide range of publications, methods, and expert resources that are well-known and common in other countries.As it proceeds through a tunnel of cyclical progress, English has become the de facto language of the whole developing world in the twenty-first century. English has become the major language used for successful worldwide communication, whether in commercial, healthcare, transportation, technical skills, trade, art, music, and literature, or advertising. Thus,this study focuses on exploring the unique qualities of the English as a linguistic medium, which is currently a dominant and intriguing medium of literal and professional communication.This research study has utilized the qualitative research method. This study is based on secondary sources. The results of the study elucidates that English has become the dominant language for successful worldwide communication in all disciplines, including business, medicine, transportation, technology, trade, art, literature and branding.